“ Estudio Y Diagnostico De Modos De Falla En El Sistema De Distribución De Las Empresas Del Sector Electrico En El Valle Del Cauca” (2012)
This paper documents the various failure modes that occur in the distribution system electrical, where it shows the causes for which such failures may occur and their possible consequences and solutions. The document also presents a statistical analysis where is possible to see which are the most usual maintenance tasks performed in the area, and what are the substations that have more failure modes.